PENGARUH KUALITAS PELAYANAN, LOKASI, EFISIENSI SISTEM ANTRIAN DAN FASILITAS TEKNOLOGI TERHADAP KEPUASAN PELANGGAN DI KANTOR SAMSAT KABUPATEN POHUWATO - Yakup, Yakup; R. Karundeng, Deby; Afan Suyanto, Mohamad; Safril, Sandi; Ishak, Olfin (Gapenas Publisher, 2024)
This study aims to examine the effect of service quality, location, queue system efficiency, and technological facilities on customer satisfaction at the SAMSAT Office of Pohuwato Regency. Using multiple linear regression analysis, the results indicate that service quality and technological facilities have a positive and significant impact on customer satisfaction. Enhancing these two variables can directly improve customer satisfaction levels. In contrast, although location and queue system efficiency have a positive impact, their effects are not significant. Overall, all four variables have a positive simultaneous effect on customer satisfaction, with service quality and technological facilities being the dominant factors. These findings emphasize the importance of organizations focusing on improving service quality and technological facilities to enhance customer satisfaction sustainably.